Field Validation for the Constructability of Exposed Aggregate Concrete Overlay - Jaehoon Kim; Makara Rith; Seung Woo Lee; Young Kyu Kim (Advances in Civil Engineering)
Functional performance of existing concrete pavement is necessarily improved to maintain the low tire-pavement noise and the long-term skid resistance. Thus, exposed aggregate concrete overlay is introduced since these high functional performances are expected. Its surface texture requires the removal of cement mortar to expose the aggregates. This technique results a durable surface texture and an effective surface drainage through the random shape of aggregates. In Korea, concrete overlay is allowed to construct between 200 and 400 meters per day. This concrete amount is insufficient to use batch plant. Therefore, mobile mixer is employed to supply a consistent quality and on-time production. In addition, surface texture of this overlay method is significantly related to the reduction of tire-pavement noise. Accordingly, outcome of surface texture should be validated in the real field construction. This study intended to verify the constructability of exposed aggregate concrete overlay using mobile mixer for concrete production and deck finisher for concrete placement to acquire the surface texture and structural strengths. Surface texture and concrete strengths from mock-up and laboratory tests were measured and compared with design criteria. This research indicated that the suggested equipment and construction procedure can efficiently maintain the required surface texture of EACO for low tire-pavement noise and the adequate strengths for early traffic opening.